Method for separating hexafluoropropylene and octafluoropropane
By using metal organic frame materials as adsorbents, using their specific pore size and intermolecular interaction forces, the problem of difficult separation of hexafluoropropylene and octafluoropropane in the prior art is solved, and an efficient and stable gas separation effect is achieved.
Patent Information
- Application Number
- CN202510237884.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-02-28
AI Technical Summary
It is difficult to effectively separate hexafluoropropylene and octafluoropropane in the prior art. The physical and chemical properties of these two gases are similar, resulting in large energy consumption of distillation, high equipment investment, and the existing adsorbents have poor separation effect on them.
Adsorbents containing metal organic frame materials are used to achieve adsorption separation of hexafluoropropylene and octafluoropropane through the specific pore size and intermolecular interaction force of the metal organic frame materials. Metal organic frame materials are three-dimensional or two-dimensional network frame structures formed by transition metal ions and organic ligands through coordination bonds or intermolecular forces, and the pore size is about 0.50-0.70 nm.
It achieves efficient separation of hexafluoropropylene and octafluoropropane. The adsorbent has high selectivity for the two gases, and the separation effect is better than that of most adsorbent materials. The material structure is stable and has good regeneration and circulation performance.
Smart Images

Figure CN119899085A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of adsorption separation, and in particular to a method for separating hexafluoropropylene and octafluoropropane. Background Art
[0002] Electronic specialty gases are essential key raw materials for the development of integrated circuits, microelectronics, optoelectronics and other electronic industries. The purity of electronic specialty gases directly affects the yield and reliability of optoelectronic and microelectronic components, and is of great significance to the quality and performance of semiconductor integrated circuit chips. Octafluoropropane (C3F8), also known as perfluoropropane, is a halogenated hydrocarbon with good chemical stability and thermal stability. It has attracted much attention due to its non-toxic and odorless, strong stability, good thermal conductivity, good electrical insulation and physiological drug resistance. In recent years, octafluoropropane has been widely used in the field of semiconductor manufacturing due to its good etching and cleaning performance, relatively low atmospheric life and greenhouse effect potential. With the acceleration of the research and industrial production of chips in my country in recent years, the demand for octafluoropropane has increased year by year. As the chip process size decreases, the purity requirements for octafluoropropane are also getting higher and higher.
[0003] According to existing literature reports, the current synthetic routes of octafluoropropane include: (1) direct reaction of carbon with fluorine gas: This is a method for mass production of carbon tetrafluoride and hexafluoroethane, in which octafluoropropane is produced as a by-product with a yield of about 10%. This method is already quite mature and can be achieved by recovering octafluoropropane in the product; (2) direct fluorination of heptafluoropropane: This is a commonly used synthetic route in industry, in which octafluoropropane is prepared by the reaction of heptafluoropropane (C3HF7) with fluorine gas. The raw material heptafluoropropane of this method has a high purity and the purity of fluorine gas is sufficient, so it can be used directly; (3) fixed bed reaction: using CoF3 as a fluorinating agent, octafluoropropane is synthesized through a series of reactions. In this process, the crude product needs to be purified by washing, adsorption and distillation; (4) perfluoropropylene fluorination addition: This is the main process used in developed countries, in which octafluoropropane is produced by the reaction of perfluoropropylene (C3F6) with fluorine gas. In the above-mentioned synthesis methods: the direct fluorination method of heptafluoropropane has high requirements on the purity of fluorine gas, and HF may be generated during the preparation process, which is corrosive to the equipment and the environment; the fixed bed reaction method uses CoF3 as a fluorinating agent, and HF and other by-products may be generated during the reaction, which need to be purified through steps such as washing, adsorption and distillation, which increases the production cost and complexity. At the same time, the reaction mechanism is complex, and the control requirements for the reaction conditions are high, and the corrosion resistance requirements for the equipment are also high; the perfluoropropylene fluorination addition method will release a lot of heat during the reaction, which makes the reaction conditions difficult to control and poses a safety hazard. In addition, the by-products such as fluorocarbons and polymers with different carbon atoms generated by the reaction are difficult to separate, which affects the purity and yield of the product.
[0004] At present, the main methods for purifying octafluoropropane are: distillation, adsorption separation, membrane separation and catalytic conversion. Among them, distillation is one of the most widely used and mature separation processes in industry, which is suitable for separating impurity components with large boiling point differences. However, for components such as hexafluoropropylene and octafluoropropane, which have very similar physical and chemical properties and close boiling points, the distillation method has high energy consumption and high equipment investment, and it is difficult to remove trace impurities to meet electronic grade application standards. Membrane separation technology can provide a mild separation environment, which is suitable for the separation of heat-sensitive substances and molecules with large molecular size differences, but the balance between the selectivity and permeability of membrane materials has always been a key challenge restricting the development and application of membrane separation technology. At the same time, the stability and durability of the membrane are also worth considering. The catalytic conversion method is to convert impurities with a boiling point close to the target product into impurities with a large boiling point difference through chemical conversion. This method is only effective for certain impurities, and other side reactions are likely to occur during the chemical reaction to reduce the yield. In comparison, the adsorption separation method is simple to operate, has low operating costs, and the adsorbent is easy to recover. It is an environmentally friendly green separation technology. At present, the most widely used adsorbent materials are molecular sieves, activated carbon and carbon molecular sieves, but the above adsorbents have poor separation effects on hexafluoropropylene and octafluoropropane. It is still challenging to develop adsorbent materials with high adsorption selectivity for hexafluoropropylene and octafluoropropane mixed gas under normal pressure. Summary of the invention
[0005] In view of the above problems, the present application proposes a method for separating hexafluoropropylene and octafluoropropane.
[0006] Specifically, the present application provides a method for separating hexafluoropropylene and octafluoropropane, which comprises: using an adsorbent comprising a metal organic framework material to perform adsorption separation on a mixed gas comprising hexafluoropropylene and octafluoropropane, wherein the metal organic framework material comprises metal ions and organic ligands,
[0007] Wherein, the organic ligand includes a compound shown in formula I,
[0008]
[0009] In formula I, R is selected from hydrogen, halogen or C1-C4 alkyl;
[0010] The metal ions are selected from one or more of transition metal ions and alkaline earth metal ions.
[0011] In some embodiments, in Formula I, R is selected from hydrogen, fluorine, chlorine, bromine, methyl, ethyl, or propyl.
[0012] In some embodiments, the organic ligand is 2,5-dihydroxy-1,4-benzoquinone (H2dhbq).
[0013] In some embodiments, the metal ion is selected from one or more of scandium ion, vanadium ion, zinc ion, iron ion, cobalt ion, nickel ion, magnesium ion, tin ion, manganese ion, copper ion, zirconium ion or titanium ion.
[0014] In some embodiments, the metal ions are selected from one or more of zinc ions, magnesium ions, iron ions, cobalt ions, and manganese ions.
[0015] The metal organic framework material prepared in the present application is a three-dimensional or two-dimensional network framework structure formed by transition metal ions or alkaline earth metal ions and organic ligands (such as 2,5-dihydroxy-1,4-benzoquinone) through coordination bonds or intermolecular forces, and the pore size is about 0.50-0.70nm. Hexafluoropropylene with a smaller molecular diameter can have a strong interaction force and hydrogen bond with the open metal sites and hydrogen atoms in the material framework, while octafluoropropane with a larger molecular diameter is difficult to enter the pores. The intermolecular interaction and molecular exclusion mechanism make the adsorption amount of the two gases on the surface of the material significantly different. When the mixed gas passes through the adsorption device, the octafluoropropane has a weak force and a small adsorption capacity, and it flows out from the outlet of the device first. The adsorption force between hexafluoropropylene and the metal organic framework material is strong and the adsorption capacity is large, and it takes longer to flow out from the outlet of the device, thereby achieving the separation of hexafluoropropylene and octafluoropropane.
[0016] In some embodiments, the temperature of the adsorption separation is -5°C to 50°C, for example, 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C or any value therebetween. In some embodiments, the temperature of the adsorption separation is 0°C to 40°C. In some embodiments, the temperature of the adsorption separation is 20°C to 30°C.
[0017] In some embodiments, the pressure of the adsorption separation is 100 kPa-1000 kPa, for example, 150 kPa, 200 kPa, 250 kPa, 300 kPa, 400 kPa, 500 kPa, 600 kPa, 700 kPa, 800 kPa, 900 kPa or any value therebetween. In some embodiments, the pressure of the adsorption separation is 100 kPa-300 kPa.
[0018] In some embodiments, the temperature of the adsorption separation is 25° C., and the total pressure of the mixed gas is 100 kPa. The separation in the method provided in the present application can be carried out at normal pressure, which exceeds most existing adsorbents.
[0019] In some embodiments, the pore size of the metal organic framework material is 0.4nm-1.0nm, for example, 0.45nm, 0.5nm, 0.53nm, 0.55nm, 0.57nm, 0.59nm, 0.6nm, 0.63nm, 0.65nm, 0.67nm, 0.69nm, 0.7nm, 0.75nm, 0.8nm, 0.85nm, 0.9nm, 0.95nm or any value therebetween. In some embodiments, the pore size of the metal organic framework material is 0.5nm-0.7nm.
[0020] In some embodiments, the specific surface area of the metal organic framework material is 100-1000m 2 / g, for example, 150m 2 / g, 200m 2 / g, 250m 2 / g、300m 2 / g, 350m 2 / g, 400m 2 / g, 450m 2 / g、500m 2 / g, 550m 2 / g、600m 2 / g, 650m 2 / g、700m 2 / g, 750m 2 / g、800m 2 / g, 850m 2 / g、900m 2 / g or 950m 2 In some embodiments, the specific surface area of the metal organic framework material is 150 m 2 / g-800m 2 / g.
[0021] In some embodiments, the micropore specific surface area of the metal organic framework material is 100-800m 2 / g, for example, 150m 2 / g, 200m 2 / g, 250m 2 / g、300m 2 / g, 350m 2 / g, 400m 2 / g, 450m 2 / g、500m 2 / g, 550m 2 / g、600m 2 / g, 650m 2 / g、700m 2 / g or 750m 2 In some embodiments, the micropore specific surface area of the metal organic framework material is 120 m 2 / g-800m 2 / g.
[0022] In some embodiments, the metal organic framework material has a microporosity of 70%-98%, such as 72%, 75%, 77%, 79%, 80%, 83%, 85%, 87%, 89%, 90%, 93% or 95%. In some embodiments, the metal organic framework material has a microporosity of 75%-90%.
[0023] In the present application, the microporosity of the metal organic framework material is the ratio of the specific surface area of the micropores of the material to the surface area (total specific surface area).
[0024] In some embodiments, the metal organic framework material is in the shape of powder, sphere, column, particle or film. The metal organic framework material used in this application can be prepared into adsorption separation materials in the form of powder, sphere, column, particle or film by different processing techniques.
[0025] In some embodiments, the method for preparing the metal organic framework material comprises: reacting a metal soluble salt and a compound represented by Formula I in a solvent, and centrifuging, washing and drying the reaction product.
[0026] In the preparation process of the metal organic framework material in the present application, H2dhbq, which is cheap and easy to synthesize in the laboratory, is used as an organic ligand to react with a series of metal inorganic salts in deionized water, without using any toxic, volatile and expensive organic solvents. The raw materials for the preparation of the material are cheap, the synthesis conditions are mild, the operation is convenient, the post-treatment is simple, and the synthesis cost of the material is low. The metal organic framework material disclosed in the present application has high adsorption and separation selectivity for hexafluoropropylene and octafluoropropane, and the structure and adsorption performance of the material are stable. It can still maintain the original adsorption and separation performance when exposed to air or water vapor for a long time, and has good prospects for industrial application.
[0027] In some embodiments, the metal soluble salt is selected from one or more of chlorides, nitrates, acetates, carbonates, sulfates or perchlorates of metal ions. In some embodiments, the metal soluble salt is selected from one or more of ferric chloride, ferric nitrate, ferric acetate, ferric sulfate, ferric perchlorate, manganese chloride, manganese nitrate, manganese acetate, manganese sulfate, manganese perchlorate, zinc chloride, zinc nitrate, zinc acetate, zinc sulfate, cobalt chloride, cobalt nitrate, cobalt acetate, cobalt sulfate, magnesium chloride, magnesium nitrate, magnesium acetate and magnesium sulfate.
[0028] In some embodiments, the compound represented by Formula I is 2,5-dihydroxy-1,4-benzoquinone.
[0029] In some embodiments, the molar ratio of the metal soluble salt to the compound of Formula I is 1:(0.5-10), for example, 1:0.7, 1:1, 1:1.3, 1:1.5, 1:1.7, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:6, 1:7, 1:8, 1:9 or any value therebetween. In some embodiments, the molar ratio of the metal soluble salt to the compound of Formula I is 1:(1-3).
[0030] In some embodiments, the reaction temperature is 20° C.-120° C., for example, 30° C., 40° C., 50° C., 60° C., 70° C., 80° C., 90° C. or 100° C. In some embodiments, the reaction temperature is 60° C.-50° C. The reaction temperature affects the crystal formation process and reaction rate. Too high or too low a temperature will affect the quality and performance of the generated crystals.
[0031] In some embodiments, the reaction time is 12h-72h, for example, 15h, 20h, 25h, 30h, 35h, 40h, 45h, 50h, 55h, 60h, 65h or 70h. In some embodiments, the reaction time is 24h-30h.
[0032] In some embodiments, the reaction is carried out under stirring conditions. In some embodiments, the stirring speed is 500 rpm-1000 rpm, for example, 600 rpm, 700 rpm, 800 rpm or 900 rpm. Uneven mixing may result in irregular crystal forms of the metal organic framework material obtained by the reaction.
[0033] In some embodiments, the solvent is selected from one or more of methanol, ethanol, acetonitrile, acetone, N,N-dimethylformamide, N,N-dimethylacetamide and water, preferably water.
[0034] In some embodiments, the molar ratio of the metal soluble salt to the solvent is 1:(100-6000), for example, 1:200, 1:500, 1:700, 1:1000, 1:1500, 1:2000, 1:3000, 1:4000 or 1:5000, based on the metal ions. In some embodiments, the molar ratio of the metal soluble salt to the solvent is 1:(300-2000).
[0035] In some embodiments, the drying is vacuum drying. In some embodiments, the temperature of vacuum drying is 30°C-120°C. In some embodiments, the time of vacuum drying is 6h-24h. In some embodiments, the vacuum degree of vacuum drying is -0.1MPa to -0.08MPa.
[0036] In some embodiments, the centrifugation conditions are: 6000-10000 rpm, centrifugation for 5-15 minutes.
[0037] In some embodiments, the washing includes washing with deionized water several times until the filtrate is colorless and clear to replace the inorganic salts and organic ligands remaining in the pores, and then washing with anhydrous ethanol several times to replace the organic ligands and water remaining in the pores.
[0038] In some embodiments, the adsorption separation comprises: passing the mixed gas containing hexafluoropropylene and octafluoropropane through an adsorption tower or adsorption column filled with adsorbent material. In some embodiments, the adsorption tower may also be composed of one or more. In some embodiments, separation is achieved by using existing pressure swing adsorption or vacuum pressure swing adsorption or temperature swing adsorption.
[0039] In some embodiments, the adsorptive separation is performed using a fixed bed, wherein the adsorbent is filled in the fixed bed adsorption column.
[0040] In some embodiments, the adsorptive separation comprises the following steps:
[0041] (1) passing a mixed gas containing hexafluoropropylene and octafluoropropane through a fixed bed adsorption column, whereby strongly adsorbed hexafluoropropylene is adsorbed on the adsorbent and weakly adsorbed octafluoropropane penetrates the adsorption column, thereby obtaining weakly adsorbed octafluoropropane;
[0042] (2) Desorbing the strongly adsorbed hexafluoropropylene from the adsorbent to obtain the strongly adsorbed hexafluoropropylene.
[0043] In some embodiments, the flow rate of the mixed gas containing hexafluoropropylene and octafluoropropane through the fixed bed adsorption column is 1-100 mL / min / g adsorbent, for example, 5 mL / min / g adsorbent, 10 mL / min / g adsorbent, 20 mL / min / g adsorbent, 30 mL / min / g adsorbent, 40 mL / min / g adsorbent, 50 mL / min / g adsorbent, 60 mL / min / g adsorbent, 70 mL / min / g adsorbent, 80 mL / min / g adsorbent or 90 mL / min / g adsorbent.
[0044] In some embodiments, the method further comprises regenerating the adsorbent after the adsorptive separation is completed.
[0045] In some embodiments, the regeneration comprises heating the adsorbent to 50°C-200°C under vacuum or inert atmosphere conditions for 2h-72h. In some embodiments, the regeneration comprises maintaining the adsorbent at 5°C-30°C for 2h-72h under vacuum or inert atmosphere conditions. In some embodiments, the regeneration comprises maintaining the adsorbent at room temperature for 2h-72h under vacuum or inert atmosphere conditions.
[0046] If the heating temperature is too high or the time is too long, the adsorbent structure will be destroyed; if the temperature is too low or the time is too short, the adsorbate remaining in the adsorbent will not be completely removed.
[0047] Compared with the prior art, this application has the following advantages:
[0048] (1) The organic ligands and metal salts used in the preparation of the metal organic framework materials involved in this application are cheap and easily available, the synthesis conditions are green and mild, the purification steps are simple, and it is easy to operate and synthesize on a large scale.
[0049] (2) The metal organic framework material involved in the present application has a stable structure, extremely high air, hydrothermal and chemical stability, and has a very high adsorption and separation selectivity for a mixed gas of hexafluoropropylene and octafluoropropane.
[0050] (3) The metal organic framework material involved in this application has stable performance and good regeneration cycle performance. After multiple adsorption-regeneration cycles, it can still maintain the original separation performance. The performance in the adsorption and separation of hexafluoropropylene and octafluoropropane is far better than that of most adsorbent materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 The adsorption isotherms of the metal organic framework material in Example 1 for hexafluoropropylene and octafluoropropane are shown.
[0052] Figure 2 The adsorption isotherms of the metal organic framework material in Example 2 for hexafluoropropylene and octafluoropropane are shown.
[0053] Figure 3 The adsorption isotherms of the metal organic framework material in Example 3 for hexafluoropropylene and octafluoropropane are shown.
[0054] Figure 4 The adsorption isotherms of the metal organic framework material in Example 4 for hexafluoropropylene and octafluoropropane are shown.
[0055] Figure 5 The adsorption isotherms of the metal organic framework material in Example 5 for hexafluoropropylene and octafluoropropane are shown.
[0056] Figure 6The low-temperature nitrogen adsorption-desorption curve of the metal organic framework material in Example 1 is shown.
[0057] Figure 7 The low-temperature nitrogen adsorption-desorption curve of the metal organic framework material in Example 2 is shown.
[0058] Figure 8 The low-temperature nitrogen adsorption-desorption curve of the metal organic framework material in Example 3 is shown.
[0059] Fig. 9 The low-temperature nitrogen adsorption-desorption curve of the metal organic framework material in Example 4 is shown.
[0060] Fig.10 The low-temperature nitrogen adsorption-desorption curve of the metal organic framework material in Example 5 is shown.
[0061] Fig.11 The fixed bed breakthrough curve of the metal organic framework material in Example 1 for the mixed gas of hexafluoropropylene and octafluoropropane is shown.
[0062] Fig.12 The fixed bed breakthrough curve of the metal organic framework material in Example 2 for the mixed gas of hexafluoropropylene and octafluoropropane is shown.
[0063] Fig.13 The fixed bed penetration curve of the metal organic framework material in Example 3 for the mixed gas of hexafluoropropylene and octafluoropropane is shown.
[0064] Fig.14 The fixed bed breakthrough curve of the metal organic framework material in Example 4 for the mixed gas of hexafluoropropylene and octafluoropropane is shown.
[0065] Fig.15 The fixed bed breakthrough curve of the metal organic framework material in Example 5 for the mixed gas of hexafluoropropylene and octafluoropropane is shown.
[0066] Fig.16 The cyclic adsorption isotherms of the metal organic framework material in Example 5 for hexafluoropropylene and octafluoropropane are shown. DETAILED DESCRIPTION
[0067] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme of the embodiments of the present application will be clearly and completely described below in conjunction with the drawings of the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the described embodiments of the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0068] In the following examples and comparative examples, unless otherwise specified, pressures are gauge pressures.
[0069] Example 1
[0070] Weigh 2.5-dihydroxy-1,4-dibenzoquinone (H2dhbq, 1.5mmol, 0.21g) and zinc acetate dihydrate (Zn(CH3COO)2·2H2O, 1.5mmol, 0.33g) and dissolve in 10mL of deionized water, and heat and stir in an 80°C oil bath for 24 hours. After the reaction is completed, the sample is centrifuged and washed with deionized water several times until the supernatant is colorless and clear, and then the sample is centrifuged and washed with anhydrous ethanol several times. The washed sample is placed in a vacuum drying oven at 60°C and dried for 6 hours to obtain a metal organic framework zinc material. The obtained zinc material is then vacuum degassed at 150°C for 12 hours, followed by a low-temperature nitrogen adsorption and desorption experiment. The low-temperature nitrogen adsorption and desorption curve is shown in the following figure. Figure 6 shown.
[0071] The microporosity of the zinc material prepared in this embodiment is 82.4%, and the specific surface area is 409.39 m 2 / g, micropore specific surface area is 337.35m 2 / g, and the main pore size distribution is concentrated in the range of 0.51-0.62nm.
[0072] In order to test the adsorption and separation performance of the zinc material prepared in this example, the single-component static adsorption experiments of hexafluoropropylene and octafluoropropane gas were carried out using the zinc material prepared as the adsorbent. Specifically, 100 mg of the adsorbent was taken and the adsorption temperature was set to 25°C. Figure 1 As shown in the results, at 25°C and 1 bar, the adsorption capacity of hexafluoropropylene reached 1.86 mmol / g, while the adsorption capacity of octafluoropropane was 0.08 mmol / g. At 1 bar, the ratio of the adsorption capacity of the adsorbent material to the two gases reached 23.3.
[0073] In order to test the actual effect of the zinc material prepared in this example on the separation of hexafluoropropylene and octafluoropropane mixed gas, a fixed bed penetration experiment of hexafluoropropylene and octafluoropropane mixed gas was carried out using the above zinc material as an adsorbent. In this example, hexafluoropropylene and octafluoropropane mixed gas were adsorbed and separated, with a volume ratio of 10:90, a penetration temperature of 25°C, and a pressure of 0.1MPa. After testing, the results are as follows Fig.11 As shown, when the volume ratio of hexafluoropropylene to octafluoropropane is 10:90 and the mixed gas flow rate is 1.0 mL / min, octafluoropropane penetrates immediately, while hexafluoropropylene begins to penetrate after 96 minutes. Theoretically, 104.0 bed volumes of high-purity octafluoropropane (product purity>99.999%) can be obtained in a single adsorption, and the product yield is close to 100.0%.
[0074] Example 2
[0075] Weigh 2.5-dihydroxy-1,4-dibenzoquinone (H2dhbq, 1.5mmol, 0.21g) and magnesium acetate tetrahydrate (Mg(CH3COO)2·4H2O, 1.5mmol, 0.16g) and dissolve in 10mL of deionized water, and heat and stir in an 80°C oil bath for 24 hours. After the reaction is completed, the sample is centrifuged and washed with deionized water several times until the supernatant is colorless and clear, and then the sample is centrifuged and washed with anhydrous ethanol several times. The washed sample is placed in a vacuum drying oven at 60°C and dried for 6 hours to obtain a metal organic framework magnesium material. The obtained magnesium material is then vacuum degassed at 150°C for 12 hours, followed by a low-temperature nitrogen adsorption and desorption experiment. The low-temperature nitrogen adsorption and desorption curve is shown in the following figure. Figure 7 shown.
[0076] The metal organic framework magnesium material prepared in this embodiment has a microporosity of 83.2% and a specific surface area of 536.59 m 2 / g, micropore specific surface area is 446.67m 2 / g, and the main pore size distribution is concentrated in the range of 0.50-0.59nm.
[0077] In order to test the adsorption and separation performance of the magnesium material prepared in this example, the magnesium material prepared above was used as an adsorbent to carry out single-component static adsorption experiments of hexafluoropropylene and octafluoropropane gas. Specifically, 100 mg of the adsorbent was taken and the adsorption temperature was set to 25°C. Figure 2 The results show that at 25°C and 1 bar, the adsorption capacity of hexafluoropropylene reaches 2.26 mmol / g, while the adsorption capacity of octafluoropropane is 0.64 mmol / g. At 1 bar, the ratio of the adsorption capacity of the adsorbent material to the two gases reaches 3.5.
[0078] In order to test the actual effect of the magnesium material prepared in this embodiment on the separation of hexafluoropropylene and octafluoropropane mixed gas, a fixed bed penetration experiment of hexafluoropropylene and octafluoropropane mixed gas was carried out using the above magnesium material as an adsorbent. In this embodiment, hexafluoropropylene and octafluoropropane mixed gas were adsorbed and separated, with a volume ratio of 10:90, a penetration temperature of 25°C, and a pressure of 0.1MPa. After testing, the results are as follows Fig.12 As shown, when the volume ratio of hexafluoropropylene to octafluoropropane is 10:90 and the mixed gas flow rate is 1.0 mL / min, octafluoropropane begins to penetrate from 27 minutes, while hexafluoropropylene begins to penetrate at 63 minutes. Theoretically, 108.3 bed volumes of high-purity octafluoropropane (product purity>99.999%) can be obtained in a single adsorption, and the product yield reaches 57.1%.
[0079] Example 3
[0080] Weigh 2.5-dihydroxy-1,4-dibenzoquinone (H2dhbq, 1.5mmol, 0.21g) and iron acetate tetrahydrate (Fe(CH3COO)2·4H2O, 1.5mmol, 0.26g) and dissolve them in 10mL of deionized water, and heat and stir in an 80°C oil bath for 24 hours. After the reaction is completed, the sample is centrifuged and washed with deionized water several times until the supernatant is colorless and clear, and then the sample is centrifuged and washed with anhydrous ethanol several times. The washed sample is placed in a vacuum drying oven at 60°C and dried for 6 hours to obtain a metal-organic framework iron material. The obtained iron material is then vacuum degassed at 150°C for 12 hours, followed by a low-temperature nitrogen adsorption and desorption experiment. The low-temperature nitrogen adsorption and desorption curve is shown in the following figure. Figure 8 shown.
[0081] The microporosity of the iron material prepared in this embodiment is 78.0%, and the specific surface area is 191.51 m 2 / g, micropore specific surface area is 149.44m 2 / g, and the main pore size distribution is concentrated in the range of 0.52-0.60nm.
[0082] In order to test the adsorption and separation performance of the iron material prepared in this example, the iron material prepared as above was used as an adsorbent to carry out single-component static adsorption experiments of hexafluoropropylene and octafluoropropane gas. Specifically, 100 mg of the adsorbent was taken and the adsorption temperature was set to 25°C. Figure 3 As shown in the results, at 25°C and 1 bar, the adsorption capacity of hexafluoropropylene reached 0.57 mmol / g, while the adsorption capacity of octafluoropropane was 0.04 mmol / g. At 1 bar, the ratio of the adsorption capacity of the adsorbent material to the two gases reached 14.3.
[0083] In order to test the actual effect of the iron material prepared in this embodiment on the separation of hexafluoropropylene and octafluoropropane mixed gas, a fixed bed penetration experiment of hexafluoropropylene and octafluoropropane mixed gas was carried out using the above iron material as an adsorbent. In this embodiment, hexafluoropropylene and octafluoropropane mixed gas were adsorbed and separated, with a volume ratio of 10:90, a penetration temperature of 25°C, and a pressure of 0.1MPa. After testing, the results are as follows Fig.13 As shown, when the volume ratio of hexafluoropropylene to octafluoropropane is 10:90 and the mixed gas flow rate is 1.0 mL / min, octafluoropropane penetrates immediately, while hexafluoropropylene begins to penetrate after 18 minutes. Theoretically, 25.4 bed volumes of high-purity octafluoropropane (product purity>99.999%) can be obtained in a single adsorption, and the product yield reaches 100.0%.
[0084] Example 4
[0085] Weigh 2.5-dihydroxy-1,4-dibenzoquinone (H2dhbq, 1.5mmol, 0.21g) and cobalt chloride hexahydrate (CoCl2·6H2O, 1.5mmol, 0.36g) and dissolve them in 10mL of deionized water, and heat and stir in an 80°C oil bath for 24 hours. After the reaction is completed, the sample is centrifuged and washed with deionized water several times until the supernatant is colorless and clear, and then the sample is centrifuged and washed with anhydrous ethanol several times. The cleaned sample is placed in a vacuum drying oven at 60°C and dried for 6 hours to obtain a metal organic framework cobalt material. The obtained cobalt material is then vacuum degassed at 150°C for 12 hours, followed by a low-temperature nitrogen adsorption and desorption experiment. The low-temperature nitrogen adsorption and desorption curve is shown in the following figure. Fig. 9 shown.
[0086] The microporosity of the cobalt material prepared in this embodiment is 86%, and the specific surface area is 284.81 m 2 / g, micropore specific surface area is 245.2m 2 / g, and the main pore size distribution is concentrated in the range of 0.54-0.68nm.
[0087] In order to test the adsorption and separation performance of the cobalt material prepared in this example, the cobalt material prepared above was used as an adsorbent to carry out single-component static adsorption experiments of hexafluoropropylene and octafluoropropane gas. 100 mg of the adsorbent was taken and the adsorption temperature was set to 25°C. Figure 4 As shown in the results, at 25°C and 1 bar, the adsorption capacity of hexafluoropropylene reached 1.80 mmol / g, while the adsorption capacity of octafluoropropane was 0.05 mmol / g. At 1 bar, the ratio of the adsorption capacity of the adsorbent material for the two gases reached 3600.
[0088] In order to test the actual effect of the iron material prepared in this embodiment on the separation of hexafluoropropylene and octafluoropropane mixed gas, a fixed bed penetration experiment of hexafluoropropylene and octafluoropropane mixed gas was carried out using the above iron material as an adsorbent. In this embodiment, hexafluoropropylene and octafluoropropane mixed gas were adsorbed and separated, with a volume ratio of 10:90, a penetration temperature of 25°C, and a pressure of 0.1MPa. After testing, the results are as follows Fig.14 As shown, when the volume ratio of hexafluoropropylene to octafluoropropane is 10:90 and the mixed gas flow rate is 1.0 mL / min, octafluoropropane penetrates immediately, while hexafluoropropylene begins to penetrate after 69 minutes. Theoretically, 87.7 bed volumes of high-purity octafluoropropane (product purity>99.999%) can be obtained in a single adsorption, and the product yield reaches 100.0%.
[0089] Example 5
[0090] Weigh 2.5-dihydroxy-1,4-dibenzoquinone (H2dhbq, 1.5mmol, 0.21g) and manganese acetate tetrahydrate (Mn(CH3COO)2·4H2O, 1.5mmol, 0.37g) and dissolve them in 10mL of deionized water, and heat and stir in an 80°C oil bath for 24 hours. After the reaction is completed, the sample is centrifuged and washed with deionized water several times until the supernatant is colorless and clear, and then the sample is centrifuged and washed with anhydrous ethanol several times. The washed sample is placed in a vacuum drying oven at 60°C and dried for 6 hours to obtain a metal-organic framework manganese material. The obtained manganese material is then vacuum degassed at 150°C for 12 hours, followed by a low-temperature nitrogen adsorption and desorption experiment. The low-temperature nitrogen adsorption and desorption curve is shown in the following figure. Fig.10 shown.
[0091] The microporosity of the manganese material prepared in this embodiment is 85.0%, and the specific surface area is 329.98 m 2 / g, micropore specific surface area is 280.36m 2 / g, and the main pore size distribution is concentrated in the range of 0.53-0.59nm.
[0092] In order to test the adsorption and separation performance of the manganese material prepared in this example, single-component static adsorption experiments of hexafluoropropylene and octafluoropropane gas were carried out using the manganese material prepared as the adsorbent. Specifically, 100 mg of the adsorbent was taken and the adsorption temperature was set to 25°C. Figure 5 As shown in the results, at 25°C and 1 bar, the adsorption capacity of hexafluoropropylene reached 2.01 mmol / g, while the adsorption capacity of octafluoropropane was 0.18 mmol / g. At 1 bar, the ratio of the adsorption capacity of the adsorbent material to the two gases reached 11.2.
[0093] In order to test the actual effect of the manganese material prepared in this example on the separation of hexafluoropropylene and octafluoropropane mixed gas, a fixed bed penetration experiment of hexafluoropropylene and octafluoropropane mixed gas was carried out using the above manganese material as an adsorbent. In this example, hexafluoropropylene and octafluoropropane mixed gas were adsorbed and separated, with a volume ratio of 10:90, a penetration temperature of 25°C, and a pressure of 0.1MPa. After testing, the results are as follows Fig.15 As shown, when the volume ratio of hexafluoropropylene to octafluoropropane is 10:90 and the mixed gas flow rate is 1.0 mL / min, octafluoropropane penetrates immediately, while hexafluoropropylene begins to penetrate at 105 minutes. Theoretically, 109.4 bed volumes of high-purity octafluoropropane (product purity>99.999%) can be obtained in a single adsorption, and the product yield is close to 100.0%.
[0094] like Fig.16 As shown, after undergoing five adsorption-regeneration breakthrough cycles, the adsorption performance of the metal organic framework material remains stable and the mixed gas can still be effectively separated.
[0095] The preferred embodiments of the present application are described in detail above, but the present application is not limited thereto. Within the technical concept of the present application, the technical solution of the present application can be subjected to a variety of simple modifications, including combining various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed in the present application and belong to the protection scope of the present application.
Claims
1. A method for separating hexafluoropropylene and octafluoropropane, comprising: Adsorbents containing metal organic framework materials are used to separate mixed gases containing hexafluoropropylene and octafluoropropane by adsorption; The metal organic framework material comprises metal ions and organic ligands. Wherein, the organic ligand includes a compound shown in formula I, In formula I, R is selected from hydrogen, halogen or C1-C4 alkyl; The metal ions are selected from one or more of transition metal ions and alkaline earth metal ions.
2. The method according to claim 1, characterized in that: The metal ion is selected from one or more of scandium ion, vanadium ion, zinc ion, iron ion, cobalt ion, nickel ion, magnesium ion, tin ion, manganese ion, copper ion, zirconium ion or titanium ion, preferably selected from one or more of zinc ion, magnesium ion, iron ion, cobalt ion and manganese ion; and / or The organic ligand is 2,5-dihydroxy-1,4-benzoquinone.
3. The method according to claim 1 or 2, characterized in that: The temperature of the adsorption separation is -5°C to 50°C, preferably 0°C to 40°C, and more preferably 20°C to 30°C.
4. The method according to any one of claims 1 to 3, characterized in that The pressure of the adsorption separation is 100 kPa-1000 kPa, preferably 100 kPa-300 kPa.
5. The method according to any one of claims 1 to 4, characterized in that The pore size of the metal organic framework material is 0.4nm-1.0nm, preferably 0.5nm-0.7nm; and / or The specific surface area of the metal organic framework material is 100 m 2 / g-1000m 2 / g, preferably 150m 2 / g-800m 2 / g; and / or The micropore specific surface area of the metal organic framework material is 100 m 2 / g-800m 2 / g, preferably 120m 2 / g-500m 2 / g; and / or The microporosity of the metal organic framework material is 70%-98%, preferably 75%-90%; and / or The metal organic framework material is in the shape of powder, sphere, column, particle or film.
6. The method according to any one of claims 1 to 5, characterized in that The preparation method of the metal organic framework material comprises: reacting a metal soluble salt and a compound represented by formula I in a solvent, and centrifuging, washing and drying the reaction product; Preferably, the metal soluble salt is selected from one or more of chlorides, nitrates, acetates, carbonates, sulfates or perchlorates of metal ions, preferably selected from one or more of ferric chloride, ferric nitrate, ferric acetate, ferric sulfate, ferric perchlorate, manganese chloride, manganese nitrate, manganese acetate, manganese sulfate, manganese perchlorate, zinc chloride, zinc nitrate, zinc acetate, zinc sulfate, cobalt chloride, cobalt nitrate, cobalt acetate, cobalt sulfate, magnesium chloride, magnesium nitrate, magnesium acetate and magnesium sulfate; Preferably, the compound represented by formula I is 2,5-dihydroxy-1,4-benzoquinone.
7. The method according to claim 6, characterized in that The molar ratio of the metal soluble salt to the compound of formula I is 1:(0.5-10), preferably 1:(1-3), calculated as metal ions; the molar ratio of the metal soluble salt to the solvent is 1:(100-6000), preferably 1:(300-2000); and / or The reaction temperature is 20°C-120°C, preferably 60°C-100°C; and / or The reaction time is 12h-72h, preferably 24h-30h; and / or The reaction is carried out under stirring conditions, preferably at a stirring speed of 500 rpm-1000 rpm; and / or The solvent is selected from one or more of methanol, ethanol, acetonitrile, acetone, N,N-dimethylformamide, N,N-dimethylacetamide and water, preferably water; and / or The drying is vacuum drying. Preferably, the vacuum drying temperature is 30°C-120°C, the time is 6h-24h, and the vacuum degree is -0.1MPa to -0.08MPa.
8. The method according to any one of claims 1 to 7, characterized in that The adsorption separation is carried out using a fixed bed, wherein the adsorbent is filled in the fixed bed adsorption column, and preferably comprises the following steps: (1) passing a mixed gas containing hexafluoropropylene and octafluoropropane through a fixed bed adsorption column, whereby strongly adsorbed hexafluoropropylene is adsorbed on the adsorbent and weakly adsorbed octafluoropropane penetrates the adsorption column, thereby obtaining weakly adsorbed octafluoropropane; (2) Desorbing the strongly adsorbed hexafluoropropylene from the adsorbent to obtain the strongly adsorbed hexafluoropropylene.
9. The method according to claim 8, characterized in that The flow rate of the mixed gas containing hexafluoropropylene and octafluoropropane passing through the fixed bed adsorption column is 1-100 mL / min / g adsorbent.
10. The method according to any one of claims 1 to 9, characterized in that: The method further comprises regenerating the adsorbent after the adsorption separation is completed. Preferably, the regeneration comprises heating the adsorbent to 50°C-200°C under vacuum or inert atmosphere conditions and maintaining it for 2h-72h; or the regeneration comprises maintaining the adsorbent at 5°C-30°C under vacuum or inert atmosphere conditions for 2h-72h.
Citation Information
Patent Citations
Metal organic framework material for adsorption separation of xenon gas and krypton gas and preparation method and application thereof
CN108993417A
Method for separating methane and nitrogen gas
CN109107329A
Method for separating mixed xylene
CN113024347A
Preparation method and application of coordination polymer based on 2, 5-dichloro-3, 6-dihydroxy p-benzoquinone ligand
CN115323424A
Method for separating mixture of benzene, cyclohexane and cyclohexene
CN115745728A
Cited By
Method for separating hexafluoropropylene and octafluoropropane
CN122351961A